Effect of S-methylmethionine as a protective compound on the metabolism of agricultural plants at low temperature - Gyetvai, Edina (Acta Biologica Szegediensis, 2002)
The present research dealt primarily with a special protective mechanism which appears to be part of the defence responses of plants to low temperature. It was found that the metabolisation of S-methylmethionine (SMM) had a stimulatory effect on polyamine biosynthesis. The results proved that SMM acted via a special metabolic pathway to increase the quantities of certain polyamines (putrescine, agmatine, spermidine) known to be involved in the stabilisation of the cell environment, the macromolecules and the cell membranes. It was demonstrated that in wheat varieties, peas and maize, SMM treatment was able, to varying extents, to reduce low temperature-induced electrolyte leakage measured in terms of electrical conductivity.